1996
DOI: 10.1126/science.273.5279.1225
|View full text |Cite
|
Sign up to set email alerts
|

Tourette Syndrome: Prediction of Phenotypic Variation in Monozygotic Twins by Caudate Nucleus D2 Receptor Binding

Abstract: Tourette syndrome, a chronic tic disorder with autosomal dominant inheritance, exhibits considerable phenotypic variability even within monozygotic twin pairs. The origins of this variability remain unclear. Recent findings have implicated the caudate nucleus as a locus of pathology, and pharmacological evidence supports dopaminergic involvement. Within monozygotic twins discordant for Tourette syndrome severity, differences in D2 dopamine receptor binding in the head of the caudate nucleus predicted differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
4

Year Published

1998
1998
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(103 citation statements)
references
References 26 publications
3
93
0
4
Order By: Relevance
“…An early study of monozygotic twins discordant for TS severity found evidence in affected twins of increased D 2 receptor binding in the head of the CN, but not putamen, which predicted disease severity [634]. Single-photon emission computed tomography investigations in TS have found higher DAT binding in the right caudate [635], the striatum [636-639], the putamen after amphetamine challenge [640], and the basal ganglia [641].…”
Section: Reviewmentioning
confidence: 99%
“…An early study of monozygotic twins discordant for TS severity found evidence in affected twins of increased D 2 receptor binding in the head of the CN, but not putamen, which predicted disease severity [634]. Single-photon emission computed tomography investigations in TS have found higher DAT binding in the right caudate [635], the striatum [636-639], the putamen after amphetamine challenge [640], and the basal ganglia [641].…”
Section: Reviewmentioning
confidence: 99%
“…Ten pairs of MZ twins discordant for risk of anxiety and depression were found to have reduced temporal lobe volumes in the affected twin [deGeus et al, 2007]. MZ twins discordant for Tourette syndrome show discordant D2 dopamine receptor binding in the head of the caudate nucleus [Wolf et al, 1996]. (5) Neoplastic diseases.…”
Section: Other Examples Of Discordancementioning
confidence: 99%
“…Increased white matter and asymmetry in the frontal lobe was shown in TS (Hong et al 2002). Also, reduced volume, abnormal asymmetries (Hyde et al 1995;Peterson et al 1993;Singer et al 1993) as well as increased dopamine binding within the caudate nucleus (Malison et al 1995;Wolf et al 1996) have been observed in TS. In addition, abnormal blood Xow was found in both basal ganglia and the frontal lobe in patients with TS (Buckingham et al 1993;Diler et al 2002).…”
Section: Introductionmentioning
confidence: 99%